Pollution along the Congo Town bay and Connaught Hospital bay, Freetown, Sierra Leone - Ronnie, A. D. Frazer-Williams; Mansa-Musa, Safea; Sorie, Ibrahim (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
There is increasing concern over metal tins and scraps that litter much of the coastline, dumpsites and associated environments of Freetown as a result of poor waste management. Al, Cu and Zn were assessed for their level at two sites, back of the main central government hospital (Connaught Hospital) and the estuary of Congo Town along the Central-West coastline of Freetown. Three sets each of soil, sediment, and water samples were collected between January and August 2011. Soil and sediment samples were digested prior to metal determination in accordance to standard methods. The results were, Congo Town: Al = 20.8±4.8, Zn = 1.8±1.2, Cu = 11.4± 7.6 mg Kg-1 for soil samples and Al = 20.0±5.0, Zn = 2.7±0.8, Cu = 11.3±4.4 mg Kg-1 for sediment samples whilst for the back of Connaught hospital: Al = 8.9±8.2, Zn = 1.8±0.8, Cu = 13.7±8.8 mg Kg-1 for soil samples and Al = 41.0±23, Zn = 1.5±0.4, Cu = 12.2±8;9 mg Kg-1 for sediment samples. Metal concentration (mg/L) of water samples collected at the sites were: Al = 0.27 ± 0.1, Zn = 0.52 ± 0.4, Cu = 1.04 ± 0.6 for the Congo Town bay whilst at the Connaught Hospital bay, Al = 1.10 ± 0.3, Zn = 0.21 ± 0.1, Cu = 2.06 ± 1.5. pH of soil and sediment at both sites was relatively neutral but water samples at both sites were slightly alkaline (7.8±0.2 and 7.7±0.2 for Congo Town and Connaught respectively). Results of the study raises concern of aluminium toxicity in Freetown aquatic ecosystem.